الخطط الاستراتيجية لإدارة الأزمات الصحية في السنة النبوية دراسة موضوعية: Strategic Plans for Managing Health Crises in the Sunnah: An Objective Study - صالح عبدالكريم البلوشي, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص يهدف هذا البحث إلى بيان عناية السنة عموما بالخطط الاستراتيجية لإدارة الأزمات، وخصوصا الخطط الاستراتجية الوقائية والعلاجية لإدارة الأزمات الصحية، حيث أن تسليط الضوء على تأصيل إدارة الأزمات الصحية في السنة النبوية أصبح أمرا ضروريا مع كثرة الأوبئة والأزمات الصحية العالمية، ويعمل البحث على تحرير: هل السنة اعتنت بوضع الخطط الاستراتيجية للوقاية من الأمراض، وهل السنة أيضا اعتنت ببيان الخطط الاستراتيجية للعلاج في خضم الأزمات الصحية. فجاء هذا البحث دراسة حديثية موضوعية حول :" الخطط الاستراتيجية لإدارة الأزمات الصحية في السنة النبوية "، لنصل إلى أن السنة النبوية تميزت بمعالم بارزة في إدارة الأزمات، ومن أهم هذه المعالم بث روح التفاؤل والإيجابية، والتريث والتأني في الموقف، وحسن إدارة الخبر، والاستشارة والاستخارة قبل اتخاذ القرار، والتفكير في المآلات، واللجوء إلى الله بالدعاء مع أخذ الأسباب. وأن السنة رسمت ملامح الخطط الاستراتيجية الوقائية لإدارة الأزمات الصحية، كالتذكير بأهمية الصحة وحفظ النفس، ونشر الوعي الغذائي والبيئي، والعناية المتكاملة بالصحة النفسية والرياضة البدنية والنظافة الشخصية؛ لما لها من أثر في التحصين أمام الأزمات الصحية. وتضمنت السنة النبوية الخطط الاستراتيجية العلاجية لإدارة الأزمات الصحية، فقررت المسؤولية الطبية، ودعت للبحث عن العلاجات واللقاحات للأوبئة والأمراض، وعززت التفاؤل بالشفاء والأخذ بأسباب العلاج، كما أكدت مفهوم الحجر الصحي، وأقرت إيجاد الرعاية الصحية المتنوعة والمتكاملة، وسهلت سبل التأهيل الطبي بعد الإصابة بالأمراض والأوبئة. Abstract This research aims to demonstrate the concern of the Sunnah in general with strategic plans for crisis management, especially the preventive and curative strategic plans for the management of health crises, as shedding light on the rooting of health crisis management in the Prophetic Sunnah has become a necessity with the large number of epidemics and global health crises, and the research works on editing: The Sunnah took care of developing strategic plans for the prevention of diseases, and the Sunnah also took care of explaining the strategic plans for treatment in the midst of health crises. So this research came as an objective modern study on: “Strategic plans for managing health crises in the Sunnah of the Prophet,” to arrive at that the Prophetic Sunnah was distinguished by prominent landmarks in crisis management. And istikhaarah before making a decision, and thinking about the consequences, and resorting to God in supplication while taking the reasons. And that the Sunnah drew the features of preventive strategic plans to manage health crises, such as reminding the importance of health and self-preservation, spreading nutritional and environmental awareness, and integrated care for mental health, physical sports and personal hygiene; Because of its impact on immunization in the face of health crises.The Prophetic Sunnah included strategic treatment plans for managing health crises, decided medical responsibility, called for the search for treatments and vaccines for epidemics and diseases, and promoted optimism for recovery and the introduction of the causes of treatment, as well as confirmed the concept of quarantine, approved the creation of diverse and integrated health care, and facilitated medical rehabilitation after diseases and epidemics.